2017
DOI: 10.1080/01629778.2017.1394699
|View full text |Cite
|
Sign up to set email alerts
|

Rudolf Kjellén: geopolitiken och konservatismen edited by Ragnar Björk, Bert Edström and Thomas Lundén Stockholm, Hjalmarson & Högberg, 2014.337 pp., 198 kr, ISBN 978-91-7224-196-1.

Abstract: The Swedish political scientist, geographer and politician Rudolf Kjellén (1864-1922) was an original, even pioneering thinker for his time. He is best known for his grand theory of statehood, abandoning the narrowly legal definition of the state and choosing instead to define and analyze states as something akin to living organisms (although this generalization hardly does his views full justice). However, Kjellén's ideas largely fell out of favor after his death and even more so after World War II, when his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Their simulation study revealed that in regional index-flood estimation, the method of probability-weighted moments is preferable to the method of moment estimation with regard to bias and RMSE (14). Kuldkepp in a study on watersheds located in arid areas of Nevada State, presented a new method called hybrid method to estimate peak flood discharge in areas with deficient hydrologic statistics (15). Kjeldsen et al, in a flood frequency analysis in South Africa, suggested that the effective factors in the peak flood discharge like the physiographic and climatic characteristics including longitude, latitude, watershed area, mean annual rainfall, rainfall concentration and soil compaction coefficient (16).…”
Section: Introductionmentioning
confidence: 99%
“…Their simulation study revealed that in regional index-flood estimation, the method of probability-weighted moments is preferable to the method of moment estimation with regard to bias and RMSE (14). Kuldkepp in a study on watersheds located in arid areas of Nevada State, presented a new method called hybrid method to estimate peak flood discharge in areas with deficient hydrologic statistics (15). Kjeldsen et al, in a flood frequency analysis in South Africa, suggested that the effective factors in the peak flood discharge like the physiographic and climatic characteristics including longitude, latitude, watershed area, mean annual rainfall, rainfall concentration and soil compaction coefficient (16).…”
Section: Introductionmentioning
confidence: 99%